Pregnancy loss: French clinical practice guidelines. (June 2016) - Huchon, C.; Deffieux, X.; Beucher, G.; Capmas, P.; Carcopino, X.; Costedoat-Chalumeau, N.; Delabaere, A.; Gallot, V.; Iraola, E.; Lavoue, V.; Legendre, G.; Lejeune-Saada, V.; et al.
Abstract: In intrauterine pregnancies of uncertain viability with a gestational sac without a yolk sac (with a mean of three orthogonal transvaginal ultrasound measurements <25 mm), the suspected pregnancy loss should only be confirmed after a follow-up scan at least 14 days later shows no embryo with cardiac activity (Grade C). In intrauterine pregnancies of uncertain viability with an embryo <7 mm on transvaginal ultrasound, the suspected pregnancy loss should only be confirmed after a follow-up scan at least 7 days later (Grade C). In pregnancies of unknown location after transvaginal ultrasound (i.e. not visible in the uterus), a threshold of at least 3510 IU/l for the serum human chorionic gonadotrophin assay is recommended; above that level, a viable intrauterine pregnancy can be ruled out (Grade C). Postponing conception after an early miscarriage in women who want a new pregnancy is not recommended (Grade A). A work-up for women with recurrent pregnancy loss should include the following: diabetes (Grade A), antiphospholipid syndrome (Grade A), hypothyroidism with anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) antibodies (Grade A), vitamin deficiencies (B9, B12) (Grade C), hyperhomocysteinaemia (Grade C), hyperprolactinaemia (Grade B), diminished ovarian reserve (Grade C), and a uterine malformation or an acquired uterine abnormality amenable to surgical treatment (Grade C). The treatment options recommended for women with a missed early miscarriage are vacuum aspiration (Grade A) or misoprostol (Grade B); and the treatment options recommended for women with an incomplete early miscarriage are vacuum aspiration (Grade A) or expectant management (Grade A). In the absence of both chorioamnionitis and rupture of the membranes, women with a threatened late miscarriage and an open cervix, with or without protrusion of the amniotic sac into the vagina, should receive McDonald cerclage, tocolysis with indomethacin, and antibiotics (Grade C). Among women with a threatened late miscarriage and an isolated undilated shortened cervix (<25 mm on ultrasound), cerclage is only indicated for those with a history of either late miscarriage or preterm delivery (Grade A). Among women with a threatened late miscarriage, an isolated undilated shortened cervix (<25 mm on ultrasound) and no uterine contractions, daily treatment with vaginal progesterone up to 34 weeks of gestation is recommended (Grade A). Hysteroscopic section of the septum is recommended for women with a uterine septum and a history of late miscarriage (Grade C). Correction of acquired abnormalities of the uterine cavity (e.g. polyps, myomas, synechiae) is recommended after three early or late miscarriages (Grade C). Prophylactic cerclage is recommended for women with a history of three late miscarriages or preterm deliveries (Grade B). Low-dose aspirin and low-molecular-weight heparin at a preventive dose are recommended for women with obstetric antiphospholipid syndrome (Grade A). Glycaemic levels should be controlled before conception in women with diabetes (Grade A).